Pengaruh Pemanfaatan Instagram sebagai Media Komunikasi Terhadap Pemasaran Brand Hijab Ria Miranda di Kota Jambi - Lilis Andayani; Rahmi Handayani (J-MAS (Jurnal Manajemen dan Sains), 2021)
The purpose of this study was to determine the effect of using Instagram as a medium of communication on the marketing of the hijab brand Ria Miranda in Jambi City. In this study, the type of research used is quantitative research, namely in the form of data taken from the Ria Miranda Jambi Boutique. The sample of this research is the consumer of Ria Miranda Boutique in Jambi City. The sample was done by using purposive sampling method. The data were collected by using a questionnaire distributed directly to consumers as many as 32 questionnaires. The analysis technique used is a simple linear regression method, by testing the hypothesis t test. The results of this study indicate that the use of Instagram as a medium of communication has a significant positive effect on the marketing of the hijab brand Ria Miranda in Jambi City.